1998
DOI: 10.1046/j.1432-1327.1998.2530743.x
|View full text |Cite
|
Sign up to set email alerts
|

Reductive metabolism of the hypoxia marker pimonidazole is regulated by oxygen tension independent of the pyridine nucleotide redox state

Abstract: 2-Nitroimidazoles, such as pimonidazole, are reduced in cells with low oxygen tension and are, therefore, used as hypoxia markers. However, the effect of the pyridine nucleotide redox state on pimonidazole reduction is not known. Therefore, livers from fed or fasted rats were perfused with oxygen-saturated buffer containing pimonidazole (400 µM) in the presence and absence of an inhibitor of the mitochondrial respiratory chain, potassium cyanide ; these treatments were used to modulate the mitochondrial and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 12 publications
3
127
0
Order By: Relevance
“…To confirm this surprising finding, we treated Mtb-infected macrophages with pimonidazole. At oxygen tensions ≤1%, pimonidazole is reduced to a form that covalently modifies proteins, as detected by immunocytochemistry (35). Macrophages cultured at an oxygen tension of 10% showed intense pimonidazole staining, whether or not they were Mtb-infected (Fig.…”
Section: Mtb Respires Nitrate In Human Macrophages Cultured At Nonhypmentioning
confidence: 91%
“…To confirm this surprising finding, we treated Mtb-infected macrophages with pimonidazole. At oxygen tensions ≤1%, pimonidazole is reduced to a form that covalently modifies proteins, as detected by immunocytochemistry (35). Macrophages cultured at an oxygen tension of 10% showed intense pimonidazole staining, whether or not they were Mtb-infected (Fig.…”
Section: Mtb Respires Nitrate In Human Macrophages Cultured At Nonhypmentioning
confidence: 91%
“…Only one study to date has reported subnormal oxygen tension using an oxygen electrode in three long-term diabetic cat retina with non-proliferating retinopathy (24). Another report in which a non-quantitative immunochemical marker (hypoxyprobe-1) was used in diabetic mice found increased staining, although the interpretation of these data is somewhat unclear as the staining did not appear to be related to capillary degeneration (27,28).…”
Section: Pomentioning
confidence: 96%
“…For detection of tubular hypoxia, 60 mg/kg hypoxic probe pimonidazole (Chemicon, Temucula, CA) was injected via the tail vein 2 h before the mice were killed. 29 Kidneys were perfused with ice-cold normal saline. One kidney was fixed with 4% paraformaldehyde overnight, then 70% ethanol.…”
Section: Immunohistochemical Analysis In Anti-gbm Gnmentioning
confidence: 99%